Replication of ICP0-Null Mutant Herpes Simplex Virus Type 1 Is Restricted by both PML and Sp100 - Everett, Roger D. (American Society for Microbiology (ASM), 2008)
Herpes simplex virus type 1 (HSV-1) mutants that fail to express the viral immediate-early protein ICP0 have a pronounced defect in viral gene expression and plaque formation in limited-passage human fibroblasts. ICP0 is a RING finger E3 ubiquitin ligase that induces the degradation of several cellular proteins. PML, the organizer of cellular nuclear substructures known as PML nuclear bodies or ND10, is one of the most notable proteins that is targeted by ICP0. Depletion of PML from human fibroblasts increases ICP0-null mutant HSV-1 gene expression, but not to wild-type levels. In this study, we report that depletion of Sp100, another major ND10 protein, results in a similar increase in ICP0-null mutant gene expression and that simultaneous depletion of both proteins complements the mutant virus to a greater degree. Although chromatin assembly and modification undoubtedly play major roles in the regulation of HSV-1 infection, we found that inhibition of histone deacetylase activity with trichostatin A was unable to complement the defect of ICP0-null mutant HSV-1 in either normal or PML-depleted human fibroblasts. These data lend further weight to the hypothesis that ND10 play an important role in the regulation of HSV-1 gene expression.